Retrospeksi Ekonomi-Politik Kebijakan Pemberantasan Kemiskinan di Pedesaan - Victor A Hamel (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1999)
Using a political-economy model of analysis introduced by Uphoff and Ilchman (1972), the writer tries to analyze the "aggregate optimality" of dePelopment programmes aimed at combating poverty in Indonesia. Other than the macro analysis of development political-economy, the four micro analysis or criteria of aggregate optimality are used to evaluate the effectiveness of development programmes for the poor: market integration, assets or production factors' transfer, organisational or institutional building, and enterpreneurship improvement. Then, a retrospective evaluation is applied to some development programmes implemented during the New Order regime in Indonesia, the Bimas (Mass Guidance) programme, PKT (Integrated Regional Development) programme, PIR (Nucleic People Plantation Project), and the Inpres (Presidential Instruction) programme. It is found out from this assessment that all of the development programmes have not really able to alleviate the incidence of poverty in the regions. The Bimas, PKT, PIR and Inpress were not designed as direct attack to poverty issues and hence could not substantially improve productivity among the poor. In the process of implementation, these programme have been oriented more to economic growth and formal sectors rather than the poor people economy. The worse thing was that the programmes have created poor people dependency in terms of economic as well as political resources.